Icariin‐induced inhibition of SIRT6/NF‐κB triggers redox mediated apoptosis and enhances anti‐tumor immunity in triple‐negative breast cancer - Song, Linjiang; Chen, Xian; Mi, Ling; Liu, Chi; Zhu, Shaomi; Yang, Tianlin; Luo, Xiaohong; Zhang, Qinxiu; Lu, Hua; Liang, Xin (Cancer science, 2020)
Abnormal activation of the nuclear factor‐kappa B (NF‐κB) signaling pathway is closely implicated in triple‐negative breast cancer growth, metastasis, and tumor immune escape. In this study, the anti‐cancer effects of icariin, a natural flavonol glycoside, toward breast cancer cells and the underlying mechanisms were investigated. This investigation showed that icariin selectively inhibited proliferation and triggered apoptosis in breast cancer cells in a concentration‐ and time‐dependent manner, but exhibited little cytotoxicity in normal breast cells. Moreover, icariin induced cell apoptosis via a mitochondria‐mediated pathway, as indicated by the upregulated ratio of Bax/Bcl‐2 and reactive oxygen species induction. Importantly, icariin impaired the activation of the NF‐κB/EMT pathway, as evidenced by upregulation of SIRT6, resulting in inhibition of migration and invasion of breast cancer cells. Additionally, oss‐128167, an inhibitor of SIRT6, dramatically attenuated anti‐migration and anti‐invasion effects of icariin. Transcriptomic analysis verified that impairment of NF‐κB led to the selective function of icariin in breast cancer cells. Notably, icariin exhibited a significant tumor growth inhibition and anti‐pulmonary metastasis effect in a tumor mouse model of MDA‐MB‐231 and 4T1 cells by regulating the tumor immunosuppressive microenvironment. Together, these results showed that icariin could effectively trigger apoptosis and inhibit the migration of breast cancer cells via the SIRT6/NF‐κB signaling pathway, suggesting that icariin might serve as a potential candidate drug for the treatment of breast cancer. Icariin selectively induces redox‐dependent apoptosis and inhibits migration and invasion in breast cancer cells by impairing the activation of the NF‐κB signaling pathway. Icariin upregulated expression of SIRT6 to impair the NF‐κB/EMT pathway. Icariin exhibited a significant tumor growth inhibition and anti‐pulmonary metastasis effect in vivo by regulating the tumor immunosuppressive microenvironment.